2018
DOI: 10.1186/s41182-018-0111-z
|View full text |Cite
|
Sign up to set email alerts
|

Household ownership and utilization of insecticide-treated nets under the Regional Artemisinin Resistance Initiative in Myanmar

Abstract: BackgroundMalaria is a major public health problem in Myanmar with reported artemisinin resistance. Myanmar promotes the use of insecticide-treated nets (ITNs) through the free delivery of long-lasting insecticide nets (LLINs) with target coverage of at least 80% in moderate and high-risk areas by 2014. Migrant people are at greater risk of malaria. They have significant barriers to health care services for febrile illness and malaria. Thus, a community-based survey was conducted among the migrant population t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 17 publications
6
22
1
Order By: Relevance
“…Bed net utilization was signi cantly associated with the presence of either a pregnant mother or under ve years aged children in the household among internally displaced households in the Democratic Republic of Congo (16), household members in the Budondo sub-country in Uganda (28), a national community based survey in Madagascar (30). In agreement with our nding, bed net utilization by SAC was not affected by the presence of pregnant mother or children aged less than ve years in the household in Malawi (45) and general population in Yemen (38). In addition to the above explanation, these disparities between studies could be due to differences in the culture as pregnant women or young children might share the same sleeping place with the SAC.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Bed net utilization was signi cantly associated with the presence of either a pregnant mother or under ve years aged children in the household among internally displaced households in the Democratic Republic of Congo (16), household members in the Budondo sub-country in Uganda (28), a national community based survey in Madagascar (30). In agreement with our nding, bed net utilization by SAC was not affected by the presence of pregnant mother or children aged less than ve years in the household in Malawi (45) and general population in Yemen (38). In addition to the above explanation, these disparities between studies could be due to differences in the culture as pregnant women or young children might share the same sleeping place with the SAC.…”
Section: Discussionsupporting
confidence: 83%
“…According to this study, the bed net utilization was higher among children in rural area as compared to those in urban area. In Malawi, the bed net utilization was positively associated with being resident in urban areas but not with female gender (45) which was also similar with respect to gender in Yemen (38). In similar to our nding, gender related difference in the utilization of bed net was not seen in a community based cross-sectional study in Katakwi district in Uganda (32).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Previous studies in African countries have reported higher utilization of ITNs among children ranging from 42 to 51% [7,23]. Studies from Myanmar have also reported higher ITN utilization of 45-50% among the migrant population and the Regional Artemisinin Resistance Initiative areas of Myanmar, probably due to the increased focus of the programme through heightened routine activities and increased external funding in these high risk areas [24,25]. Reasons for poor ITN utilization among caregivers of under-five children in this study need to be explored through qualitative research.…”
Section: Discussionmentioning
confidence: 97%